Transactions on Data Hiding and Multimedia Security III - Shi, Yun Q.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2008)
Since the mid 1990s, data hiding has been proposed as an enabling technology for securing multimedia communication, and is now used in various applications including broadcast monitoring, movie fingerprinting, steganography, video indexing and retrieval, and image authentication. Data hiding and cryptographic techniques are often combined to complement each other, thus triggering the development of a new research field of multimedia security. Besides, two related disciplines, steganalysis and data forensics, are increasingly attracting researchers and becoming another new research field of multimedia security. This journal, LNCS Transactions on Data Hiding and Multimedia Security, aims to be a forum for all researchers in these emerging fields, publishing both original and archival research results. This third issue contains five contributions in the areas of steganography and digital watermarking. The first two papers deal with the security of steganographic systems; the third paper presents a novel image steganographic scheme. Finally, this volume includes two papers that focus on digital watermarking and data hiding. The fourth paper introduces and analyzes a new covert channel and the fifth contribution analyzes the performance of additive attacks against quantization-based data hiding methods.
Constructing Good Covering Codes for Applications in Steganography -- On the Use of Bhattacharyya Distance as a Measure of the Detectability of Steganographic Systems -- Secure Steganography Using Gabor Filter and Neural Networks -- Oracle Channels -- Quantization-Based Methods: Additive Attacks Performance Analysis.
Keywords: Cryptography; Data encryption (Computer science).; Data protection; Electronic data processing -- Management; Computers and civilization; Multimedia systems; Algorithms; Cryptology; Data and Information Security; IT Operations; Computers and Society; Multimedia Information Systems; Algorithms